Synthesis and biological evaluation of novel lignan glycosides as anticancer agents. (8th June 2016) - Wang, Ying; Xia, Chao; Zhang, Wei; Zhao, Yu
Abstract : Novel lignan glycosides1a –1 h as analogues of cleistanthin A were designed and synthesized. Most of these compounds displayed significant cytotoxicities against four cancer cell lines. Compound1e displayed better cytotoxicity than cleistanthin A with IC50 values from 1.0 nm to 8.3 nm . Further lysosome acidity assay disclosed that1e could totally inhibit the activity of V‐ATPase at 60 nm . Abstract : Eight lignan glycosides were synthesized. Compound1e displayed strong cytotoxicity and V‐ATPase inhibitory activity.